Diagnostic value of noninvasive comprehensive morphological and functional assessment of coronary artery disease - Mladenovic, Zorica; Đorđević Dikić, Ana; Đurić, Predrag; Angelkov Ristić, Anđelka; Dzudović, Boris; Jovic, Zoran (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Recently adopted technique, Transthoracic Doppler Echocardiography (TDE) enables the estimate of functional significance of coronary luminal narrowing. A multi-slice computed coronary angiography (MSCT), as one of the most important noninvasive methods, offers us a quite precise visualization of morphological characteristics of atherosclerotic changes in coronary arteries. We have tried to evaluate the most reliable noninvasive approach aimed at the detection of major stenosis on the left anterior descending artery (LAD) and the right coronary artery (RCA). Methods. This study involved 84 patients, with the previously detected atherosclerotic lesions on the LAD and/or RCA by MSCT. The coronary flow reserve (CFR) assessment by TDE with adenosine was obtained in LAD (n = 75); RCA (n = 61), resulting in 136 vessels subjected to the analysis. Invasive coronary angiography (ICA) was performed in all patients within 24 to 48 hours after the CFR as a reference technique. Results. The Cochrans Q test proved a significant statistical difference among these techniques in detection of a significant stenosis on the LAD and RCA (p < 0.01). Further analyses revealed a significant difference between the MSCT and CFR (p < 0.05), MSCT and ICA (p < 0.01), whereas we did not find a significant difference between the CFR and ICA (p > 0.05). The main discrepancies in results among the CFR, ICA and MSCT were noticed concerning intermediate and severe stenosis on the MSCT. The MSCT had a diagnostic accuracy for the LAD 66.67%, for the RCA 75.%, the CFR had for the LAD 90% and for the RCA 81.67%, in detection of significant stenosis. Where the consensus was reached between both techniques, diagnostic accuracy was improved for the LAD 97.33% and the RCA 90 %. Conclusion. Comprehensive noninvasive evaluation of both anatomical and functional imaging in coronary diseases makes the optimal approach for precise, noninvasive assessment of the coronary artery lesions in the coronary arteries.
Keywords: coronary artery disease; diagnosis, differential; blood flow velocity; echocardiography, doppler; multidetector computed tomography; coronary angiography; sensitivity and specificity